2017
DOI: 10.14687/jhs.v14i4.5019
|View full text |Cite
|
Sign up to set email alerts
|

Examining of the relationship between math anxiety and math achievement of elementary school students<p>İlkokul öğrencilerinin matematik kaygısı ile matematik başarıları arasındaki ilişkinin incelenmesi

Abstract: This study aims to investigate relation between math anxiety and mathmatical achievement of 3hd and 4th grade  elementary school students. The participants of the study were constituted of totally 474 students, while 288 of those were attending 3hd grade, other 186 attending 4th grade. They were used math anxiety scale (13 items) developed by Mutlu & Söylemez (2017) for 3hd and 4th grades and math achievement tests for 3hd (16 items) and 4th (24 items) grades developed by Fidan (2013) as data gathering too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Although the literature on math anxiety is largely focused on adults, recent studies have reported that some children begin to encounter the math anxiety at the elementary school level. (Krinzinger, Kaufmann & Willmes, 2009;Mutlu, Söylemez & Yasul, 2017). The findings of the study depict that the correlation level of math anxiety and math achievement is -.597 among students.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Although the literature on math anxiety is largely focused on adults, recent studies have reported that some children begin to encounter the math anxiety at the elementary school level. (Krinzinger, Kaufmann & Willmes, 2009;Mutlu, Söylemez & Yasul, 2017). The findings of the study depict that the correlation level of math anxiety and math achievement is -.597 among students.…”
Section: Discussionmentioning
confidence: 78%
“…Otherwise, early anxieties can have a snowball effect and eventually lead students to avoid mathematics courses and career options for math majors (Ramirez et al, 2013). Although many studies Mutlu, Söylemez, & Yasul, 2017;Krinzinger, Kaufmann, & Willmes, 2009;Vukovic, Kieffer, Bailey, & Harari, 2013;) confirm that math anxiety is present at high levels in primary school children, it is seen that the studies conducted at this level are relatively less when the literature of math anxiety is examined. In this context, this study aims to determine the dimensions of the relationship between math anxiety and mathematics achievement of third graders by their mathematics achievement levels.…”
Section: Figure 1 the Relationships Among Poor Mathematicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the belief that students studying at primary school level may not have mathematics anxiety, there is less study that focused on this educational level compared to others (Mutlu & Söylemez, 2018). However, in the study conducted by Mutlu et al (2017) it was determined that students studying at the 3 rd and 4 th grades of primary school have high levels of mathematics anxiety. In another study conducted at the primary education level, Yenilmez and Özbey (2006) found that students in lower grades had relatively higher levels of anxiety than students in upper grades.…”
Section: Extended Abstractmentioning
confidence: 99%
“…İlkokulda öğrenim görmekte olan öğrencilerin matematik kaygısı yaşamayabileceği düşüncesinden ötürü bu öğretim seviyesinde yapılan araştırmalar diğer öğretim seviyelerine kıyasen sayıca daha azdır (Mutlu ve Söylemez, 2018). Lakin; Mutlu, Söylemez ve Yasul (2017) tarafından gerçekleştirilen araştırmada ilkokul 3. ve 4. sınıf seviyesinde öğrenim görmekte olan öğrencilerin yüksek düzeyde matematik kaygısına sahip olduğu belirlenmiştir. Yine ilköğretim seviyesinde gerçekleştirilen bir başka araştırmada Yenilmez ve Özbey (2006), alt sınıflarda öğrenim görmekte olan öğrencilerin üst sınıflarda öğrenim görmekte olan öğrencilere nispeten daha yüksek kaygı düzeyine sahip olduklarını belirlemişlerdir.…”
Section: Introductionunclassified